Research culture in higher education: the case of a foreign language department in mexico (2014)
In the case of Mexico, until recently, many universities focused mainly on teaching, but recent changes have led to new appointments in research, administration, and community service. There now seems to be, however, a view of the predominance of research in the academic environment. Therefore, the purpose of this paper was to examine and identify, through the lens of organizational theory and a current model of research culture in an academic setting, some characteristics of the research culture in the Department of Languages and Education at a public university in Southeast Mexico. Following the international tendencies and models in higher education, we see that the research culture observed in this university resembles more a market culture than other types of culture, although some traits of hierarchy culture provide cohesion in the organization.En México, hasta hace algunas décadas, muchas universidades se enfocaban principalmente en la función de docencia. Sin embargo, recientemente se han dado cambios en la asignación de nuevas funciones: investigación, gestión y extensión. No obstante, la investigación parece tener actualmente un lugar preponderante en el ambiente académico. El propósito de este artículo es examinar e identificar, mediante la teoría de las organizaciones y un modelo actual de cultura de investigación en contextos académicos, algunas características de la cultura de la investigación en el Departamento de Lengua y Educación de una universidad pública del sureste mexicano. Siguiendo tendencias y modelos internacionales de educación superior, la cultura que se observa en esta universidad se asemeja más a una de mercado que a cualquiera de otro tipo, aunque algunos rasgos de la cultura jerárquica permiten la cohesión en la organización.